Self-reported screening practices of family physicians participating in the colorectal cancer screening program of the canton of Vaud: a cross-sectional study - Camille Poroes; Jacques Cornuz; Alexandre Gouveia; Cyril Ducros; Kevin Selby (BMC Family Practice, 2020)
Abstract Background The organized colorectal cancer (CRC) screening program in the canton of Vaud, Switzerland offers citizens the choice of the faecal immunochemical test (FIT) or colonoscopy via a visit with a family physician (FP). Given the central role of FPs in the program, this study aimed to compare their self-reported preventive practices with the objectives of the program, namely to inform patients about CRC screening and present the choice of colonoscopy and FIT, and to identify factors associated with presenting a choice of tests. Methods Mixed-methods study using an online survey and semi-structured interviews. Participants were FPs from the canton of Vaud who had included ≥1 patient in the screening program. We used multivariate logistic regression to compare FPs offering only colonoscopy to those who offered a choice of tests or FIT. Results The participation rate was 40% (177 respondents / 443 eligible). Most FPs (68%) reported informing more than 75% of eligible patients about the program. Lack of time (n = 86, 33%) was the principal reason cited for not informing patients. Regarding the screening methods, 20% (n = 36) of FPs prescribed only colonoscopy, 13% (n = 23) only FIT and 65% (n = 115) both screening methods. Predictors of offering only colonoscopy rather than a choice of screening tests included: first, FP reporting that they chose/would choose colonoscopy for themselves (OR 8.54 [95% CI 1.83–39.79, P < 0.01]); second, being > 20 years in practice (OR 4.8 [95% CI 1.3–0.17.66, P = 0.02]); and third, seeing 300 or more patients per month (OR 3.05 [95% CI 1.23–7.57, P = 0.02]). When asked what could improve the program, 17% (n = 31) wrote that patients should be informed in advance about the program by postal mail and a large-scale communication campaign. Conclusion The majority of FPs reported CRC screening practices consistent with the objectives of the program. However, to ensure that patients are well informed and to save time, all patients need to be systematically informed about the program. Further, FPs should be encouraged to offer a choice of tests.